1995
DOI: 10.1177/104063879500700303
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome: NEB-1 PRRSV Infection did not Potentiate Bacterial Pathogens

Abstract: Abstract.V. L. Cooper, A. R. Doster, R. A. Hesse, N. B. Harris A 2-phase study was conducted to evaluate the ability of the NEB-1 strain of porcine reproductive and respiratory syndrome virus (PRRSV) to potentiate common bacterial pathogens of swine. In phase I, 25 of 50 4-5-week-old specific-pathogen-free (SPF) pigs were exposed to NEB-1 PRRSV (day 0). Seven days after virus inoculation, 8 groups received 1 of 4 bacterial pathogens: Haemophihs parasuis, Streptococcus suis, Salmonella cholerasuis, and Pasteure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 8 publications
5
48
0
Order By: Relevance
“…21 Mild, prolonged, recurrent fever was reported for 4-6-weekold SPF pigs infected with a Nebraska strain of PRRSV. 2 The prolonged, mild fevers in pigs in that study were similar to the results observed in 2-weekold pigs infected with PRRSV strain NADC-8.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…21 Mild, prolonged, recurrent fever was reported for 4-6-weekold SPF pigs infected with a Nebraska strain of PRRSV. 2 The prolonged, mild fevers in pigs in that study were similar to the results observed in 2-weekold pigs infected with PRRSV strain NADC-8.…”
Section: Discussionsupporting
confidence: 74%
“…3 In contrast, other researchers were unable to demonstrate any potentiation caused by PRRSV for Haemophilus parasuis, S. suis, S. cholerasuis, and Pasteurella multocida. 2 Likewise, additional experiments have demonstrated that clinical signs or pathology due to Mycoplasma hyopneumoniae was not increased by prior PRRSV infection. 19 In terms of respiratory viral pathogens, sequential infections with PRRSV and then porcine respiratory coronavirus or with PRRSV followed later by swine influenza virus in both instances produced more severe clinical signs in pigs than when any of the 3 viruses were inoculated individually.…”
Section: Discussionmentioning
confidence: 99%
“…This ambiguity may be due to a number of factors, including the particular strain of PRRSV and/or the secondary pathogen used, the timing of such challenge and the status and immunological history of the pigs involved. Cooper et al [21] were unable to potentiate infections by challenge of 4-5 week-old specific pathogen-free (SPF) pigs with H. parasuis, S. suis, S. cholerasuis or P. multocida seven days after infection with an American PRRSV strain (AmPRRSV). But Galina et al [28], using the virulent strain of S. suis serotype 2 (DH5) in SPF piglets, observed that only those which had previously been inoculated with EuPRRSV developed clinical signs, a suppurative meningitis and large numbers of the bacteria in tissues, including the brain and meninges.…”
Section: Experimental Investigations Of An Immunomodulation Theorymentioning
confidence: 99%
“…Galina et al [43] 34,116,132]. Variable degrees of respiratory disease and growth retardation may result from infections with PRRSV followed by either PRCV or SIV [141].…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 99%